1999
DOI: 10.1128/jcm.37.6.2003-2006.1999
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Bacteroides forsythus Strains from Cat and Dog Bite Wounds in Humans and Comparison with Monkey and Human Oral Strains

Abstract: Bacteroides forsythus strains recovered from cat and dog bite wound infections in humans (n = 3), monkey oral strains (n = 3), and the human oral ATCC 43037 type strain were characterized by using phenotypic characteristics, enzymatic tests, whole cell fatty acid analysis, sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis, PCR fingerprinting, and 16S rDNA (genes coding for rRNA) sequencing. All three bite wound isolates grew on brucella agar supplemented with 5% sheep blood, vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The presence of trypsin activity is regarded as an important factor for tissue destruction in periodontal disease. In this study, B. forsythus strains (human oral isolates) were catalasenegative, whereas B. forsythus strains recovered from cat and dog bite wounds in humans were catalasepositive (Hudspeth et al, 1999). In addition, human oral isolates of B. forsythus were negative for indole production, whereas the monkey oral isolates and bitewound isolates were positive for indole production (Braham & Moncla, 1992 ;Hudspeth et al, 1999).…”
Section: Api Zym and Api An-ident Reactionsmentioning
confidence: 55%
See 4 more Smart Citations
“…The presence of trypsin activity is regarded as an important factor for tissue destruction in periodontal disease. In this study, B. forsythus strains (human oral isolates) were catalasenegative, whereas B. forsythus strains recovered from cat and dog bite wounds in humans were catalasepositive (Hudspeth et al, 1999). In addition, human oral isolates of B. forsythus were negative for indole production, whereas the monkey oral isolates and bitewound isolates were positive for indole production (Braham & Moncla, 1992 ;Hudspeth et al, 1999).…”
Section: Api Zym and Api An-ident Reactionsmentioning
confidence: 55%
“…In this study, B. forsythus strains (human oral isolates) were catalasenegative, whereas B. forsythus strains recovered from cat and dog bite wounds in humans were catalasepositive (Hudspeth et al, 1999). In addition, human oral isolates of B. forsythus were negative for indole production, whereas the monkey oral isolates and bitewound isolates were positive for indole production (Braham & Moncla, 1992 ;Hudspeth et al, 1999). 16S rDNA sequence analysis indicated that the three bitewound isolates had 99n3 % similarity to each other and 98n9 and 99n22 % similarity, respectively, to the human strain B. forsythus ATCC 43037 T and monkey oral…”
Section: Api Zym and Api An-ident Reactionsmentioning
confidence: 57%
See 3 more Smart Citations